ZEUS VERSUS PROMETEU: O embate discursivo nos artigos opinativos favoráveis e contrários à pesquisa com células-tronco embrionárias - Oliveira, José Aparecido de (2008)
From the perspective of French Discourse Analysis, this work examines specialized discourses (scientific, religious, judicial, journalistic, political) found in mass media featured articles about the scope of the Biosafety Law, mainly about ADI # 3510 judged by the Republic ex-solicitor general Claudio Fontelles. Its data are opinion featured articles issued in the papers Folha de S. Paulo and O Estado de S. Paulo, in the first semester of 2005, as well as the quoted source-documents from the Catholic Magisterium (Evangelium Vitae; Document about the Production and Scientific and Therapeutic Utilization of Human Embryonic Stem Cells; and the Donum Vitae Instruction). It s intended to verify the language modus operandi in these discourses, especially the ideological features found in their construction as persuasive elements. The research results allow the conclusion that there are dogmatic elements in these discourses, aligned with the ideology of the groups to which the writers belong, as well as mythical-philosophical-religious elements, according to the notion of Founder Discourse (Discurso Fundador) by Eni Orlandi.(AU)